Pendekatan yang Dilakukan Komisi Pengawas Persaingan Usaha Menentukan Pelanggaran dalam Hukum Persaingan Usaha - Alum Simbolon (Jurnal Hukum IUS QUIA IUSTUM, 2013)
The issue in this research is concerning with the approach used by KPPU (Commission for Business Competition) in determining the violation in business competition regulations. This aims to observe the approach is used by KPPU in determining the violation in business competition regulations. This research applies a normative-judicial method. The result of this research shows that the approach used by KPPU in determining the violation in business competition regulations in this case is judicial per se illegal approach. The implementation of per se illegal to the action of determining price conducted by KPPU is found accurate as it has been accommodated by market.